Basic reading and mathematics skills and the labour market outcomes of young people: Evidence from PISA and linked administrative data - Lisa Meehan; Gail Pacheco; Thomas Schober (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2023)
This paper uses Programme for International Student Assessment (PISA) data linked to administrative data to track the educational and labour market outcomes of young people. Students with lower skills have lower rates of participation in further education. While men with low skills out-earn their higher-skilled counterparts when they are very young, their earnings are overtaken by those with higher skills when they are in their early twenties and earn around 15 % less by the age of 25. The differences among women are substantially larger - women with low skills earn about 35 % less than their higher-skilled counterparts by age 25.
Keywords: J31; J24; I21; I26; 330; PISA; cognitive skills; education; labour market; earnings